Electromagnetic Ion-Ion Instabilities in Space Plasmas: Effects of Suprathermal Populations - Lopez-Escobar, R (Institute of Physics Publishing, 2020)
In collision-poor plasmas from space, three distinct ion-ion instabilities can be driven by the proton beams streaming along the background magnetic field: left-hand resonant, nonresonant, and right-hand resonant instabilities. These instabilities are in general investigated considering only idealized proton beams with Maxwellian velocity distributions, and ignoring the implications of suprathermal populations, usually reproduced by the Kappa power laws. Moreover, the existing theories minimize the kinetic effects of electrons, assuming them isotropic and Maxwellian distributed. In an attempt to overcome these limitations, in the present paper we present the results of an extended investigation of ion-ion instabilities, which show that their dispersion and stability properties (e.g., growth rates, wave frequencies, and the unstable wavenumbers) are highly sensitive to the influence of suprathermal populations and anisotropic electrons. These results offer valuable explanations for the origin of the enhanced low-frequency fluctuations, frequently observed in space plasmas and associated with proton beams. © 2020. The American Astronomical Society. All rights reserved..